Glacial geomorphology of the Great Glen Region of Scotland - Turner, Andrew; Woodward, John; Stokes, Chris; Ó Cofaigh, Colm; Dunning, Stuart (Journal of Maps, 2014)
This paper presents a detailed glacial Main Map of the Great Glen region of Scotland, UK, covering an area of over 6800 km2 extending from 56°34′7″ to 57°41′1″ N and from 3°44′2″ to 5°33′24″ W. This represents the first extensive mapping of the glacial geomorphology of the Great Glen and builds upon previous studies that conducted localised field mapping or ice-sheet wide mapping using remote sensing. Particular emphasis is placed on deriving medium-scale glacial retreat patterns from these data, and examining differences in landsystem assemblages across the region. Features were typically mapped at a scale of 1:8000 to 1:10,000 and will be used to investigate the pattern and dynamics of the British-Irish Ice Sheet during deglaciation. Mapping was conducted using the NEXTMap digital terrain model. In total, 17,637 glacial landforms were mapped, with 58% identified as moraines, 23% as meltwater channels, 10% as bedrock controlled glacial lineations, 3% as eskers, 2% as cirques or arêtes, 2% as kame topography or kame terraces, and 1% as drumlins. Additionally, 10 palaeo-lake shorelines were identified. Complex landform assemblages in the form of streamlined subglacial bedforms, moraines and glaciofluvial features exist across the region. Extensive subglacial meltwater networks are found over the Monadhliath Mountain Range. Transverse and longitudinal moraine ridges generally arc across valley floors or are located on valley slopes respectively. Hummocky moraines are found almost exclusively across Rannoch Moor. Finally, eskers, meltwater channels and kame landforms form spatial relationships along the axis of Strathspey. These glacial landsystems reveal the dynamics and patterns of retreat of the British-Irish Ice Sheet during the last deglaciation.